Electrophysiological Measurements of Peripheral Vestibular Function—A Review of Electrovestibulography - Brown, Daniel J.; Pastras, Christopher J.; Curthoys, Ian S. (Frontiers in Systems Neuroscience, 2017)
Electrocochleography (EcochG), incorporating the Cochlear Microphonic (CM), the Summating Potential (SP), and the cochlear Compound Action Potential (CAP), has been used to study cochlear function in humans and experimental animals since the 1930s, providing a simple objective tool to assess both hair cell and nerve sensitivity. The vestibular equivalent of ECochG, termed here Electrovestibulography (EVestG), incorporates responses of the vestibular hair cells and nerve. Few research groups have utilized EVestG to study vestibular function. Arguably, this is because stimulating the cochlea in isolation with sound is a trivial matter, whereas stimulating the vestibular system in isolation requires significantly more technical effort. That is, the vestibular system is sensitive to both high-level sound and bone-conducted vibrations, but so is the cochlea, and gross electrical responses of the inner ear to such stimuli can be difficult to interpret. Fortunately, several simple techniques can be employed to isolate vestibular electrical responses. Here, we review the literature underpinning gross vestibular nerve and hair cell responses, and we discuss the nomenclature used in this field. We also discuss techniques for recording EVestG in experimental animals and humans, and highlight how EVestG is furthering our understanding of the vestibular system.